Vaccination of goats with fresh extract from Sarcoptes scabiei confers partial protective immunity - Tarigan, Simson (Indonesian Journal of Animal and Veterinary Sciences, 2006)
Protective immunity has been known to develop in animals infested with Sarcoptes scabiei. However, our previous attempt to induce protective immunity in goats by vaccination with fractions of soluble or insoluble mite proteins had been unsuccessful. Degradation or denaturation of protective antigens occurred during vaccine preparation was suggested as one possible cause of the failure. In this study, mite proteins that used to immunise animals were prepared rapidly in order to prevent protein degradation or denaturation. About 150 mg of freshly isolated mites were rapidly homogenised, centrifuged then separated into supernatant and pellet fractions. Twenty-eight goats were allocated equally into 4 groups. Group-1 goats were vaccinated with the whole mite homogenate supernatant, group 2 with the supernatant, group 3 with the pellet, and group 4 with PBS (unvaccinated control). Vaccination was conducted three times, with three-week intervals between vaccinations, using Quil A as adjuvant, and each vaccination using fresh mite homogenates. One week after the last vaccination, all animals were challenged with approximately 2000 live mites. The severity of lesions, scored from 0 (no lesions) to 5 (>75% infested auricle affected), were determined one day, two days, then every week after challenge. Mite challenge caused the development of skin lesions in all animals. No significant differences between vaccinated and unvaccinated animals were observed in regards to the severity of lesions. However, the mite densities in vaccinated animals were significantly lower (P=0.015) than those in unvaccinated control. This study indicates that the protective antigens of S. scabiei are liable to degradation or denaturation and exist in a very low concentration or have vary low antigenicity. This implies isolation of the protective antigens by the conventional approach, fracionation of the whole mite proteins and testing each fractions in vaccination trials, is seemingly inappropriate for S. scabiei. Key Words: Sarcoptes scabiei, Vaccination, Fresh Homogenate, Partial Immunity